International Marketing Capabilities in the Digital Age: The Role of Social Media Technologies and Firm Cultural Intelligence - Hazzam, Joe (2020)
The marketing literature suggests that marketing capabilities are essential drivers of multinational organisations’ performance in foreign markets. Yet, the literature also indicates that cultural barriers represent significant challenges for the marketing department to develop international marketing capabilities that create value for foreign stakeholders. These challenges are even augmented by the emergence of social media platforms and the fast changes in the way consumers and firms communicate. Previous studies highlighted the role of marketing capabilities in explaining firms’ performance in international markets. However, little is known about the specific drivers of international marketing capabilities in digital and social media marketing and how it differs from a domestic market. In this research, the marketing capabilities and strategic management literature were used to develop a new conceptualisation of the drivers of international marketing capabilities. The thesis investigates the impact of firm cultural intelligence and social media technologies on the development of international marketing capabilities in the context of multinational enterprises that established regional offices to manage their marketing operations in foreign markets. Results explain that firm cultural intelligence and social media technologies have unique and complementary contributions to the development of international marketing capabilities, and these capabilities play an essential role in firm performance by lessening the adverse effects of foreign market turbulence. This thesis offers a new conceptualisation to the drivers of international marketing capabilities by identifying two distinct resources that have unique and complementary contributions to the development of international marketing capabilities. The firm cultural intelligence and social media technologies significantly impact the development of international marketing capabilities and might be incorporated into future MNEs’ international marketing research. The research implies that regional marketing managers should build specific processes that embed the cultural factors of their stakeholders and their regional operating markets. These culturally intelligent processes and structures contribute to the development of marketing capabilities and complement other firm’s resources, such as social media technologies.